2018
DOI: 10.1109/taes.2017.2768278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Received Signal Strength Perturbations Using Allan Variance

Abstract: Abstract-The received signal strength (RSS) of wireless signals conveys important information that has been widely used in wireless communications, localisation and tracking. Traditional RSS-based research and applications model the RSS signal using a deterministic component plus a white noise term. This paper investigates the assumption of white noise to have a further understanding of the RSS signal and proposes a methodology based on the Allan Variance (AVAR) to characterise it. Using AVAR, we model the RSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…21 The author derives a low complexity frequency domain channel estimation for faster than Nyquist (FTN) pilot transmission scenario with AWGN and whitening of colored noise. 25 Xiaogong proposed an improved Gaussian filter for nonlinear dynamic position ships to reduce the effect of cross-correlated colored noises. 23 The author proposed an improved spectrum sensing algorithm for cognitive radio to improve performance in the presence of colored noise.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…21 The author derives a low complexity frequency domain channel estimation for faster than Nyquist (FTN) pilot transmission scenario with AWGN and whitening of colored noise. 25 Xiaogong proposed an improved Gaussian filter for nonlinear dynamic position ships to reduce the effect of cross-correlated colored noises. 23 The author proposed an improved spectrum sensing algorithm for cognitive radio to improve performance in the presence of colored noise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The coefficient of various noise terms α is estimated practically for a different scenario, 25 and it is concluded that the contribution of h 0 and h −1 is dominant for a line of sight with reflection scenario, which is considered in this work. Further, the h α coefficient can be estimated by using parametric estimation techniques like the least squares (LS) algorithm.…”
Section: Allan Variancementioning
confidence: 99%
See 2 more Smart Citations
“…Presently, the measure is effectively used for quantifying the noises in the measurement of other quantities [31,32], but it is particularly useful for evaluation of inertial motion capture sensors [33,34]. Allan variance [9] is defined as:σy2(τ)=12(y(t+τ)y(t))2, where τ is the time intersample spacing, · denotes expected value.…”
Section: Introductionmentioning
confidence: 99%